2010
DOI: 10.1515/mamm.2010.040
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of Sundarbans tiger morphology

Abstract: No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…However, there is no information about the genetic makeup and diversity of the Sundarbans tigers, which are threatened by habitat destruction, prey depletion, direct tiger loss (due to human-tiger conflict), and climate change [ 4 , 9 ]. In order to investigate if Sundarbans tigers have characteristics that distinguish them from other mainland tiger populations, Barlow et al [ 10 ] compared five tiger skulls from the Bangladesh Sundarbans with 175 skulls representing nine tiger subspecies (also including three that are already extinct). Surprisingly, they found that the skulls of Sundarbans tigers were smaller and significantly different from all other subspecies.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no information about the genetic makeup and diversity of the Sundarbans tigers, which are threatened by habitat destruction, prey depletion, direct tiger loss (due to human-tiger conflict), and climate change [ 4 , 9 ]. In order to investigate if Sundarbans tigers have characteristics that distinguish them from other mainland tiger populations, Barlow et al [ 10 ] compared five tiger skulls from the Bangladesh Sundarbans with 175 skulls representing nine tiger subspecies (also including three that are already extinct). Surprisingly, they found that the skulls of Sundarbans tigers were smaller and significantly different from all other subspecies.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, Amur tigers are large and have pale orange fur, whereas tigers from the Sunda Islands tend to be smaller and have darker, thickly striped pelages [11]. Bengal tigers are the largest type [31], although tigers from the Sundarbans in Bangladesh appear smaller than other Bengal tigers [32]. The overall absence of diagnostic morphological traits supports the hypothesis that a severe late Pleistocene demographic bottleneck probably extensively reduced genetic variation in the tiger.…”
Section: Selection and Local Adaptation In Tiger Subspeciesmentioning
confidence: 95%
“…For instance, radio-collaring studies have revealed that tigers rarely cross the rivers wider than 400 m in India Sundarbans (Naha et al 2016) as well as 600 m in Bangladesh Sundarbans (Barlow 2009), suggesting that tiger movement might have been compromised by wide rivers in this mangrove forests. Several studies have highlighted the morphological adaptation (Barlow et al 2010) and genetic distinctiveness (Singh et al 2015) of the Sundarbans tigers, however none have examined the effect of barriers on the fine-scale genetic structure of the population. Understanding how landscape barriers facilitate or deter gene flow is a high priority management need for an endangered population surviving in a changing forest habitat (Sork and Waits 2010).…”
Section: Introductionmentioning
confidence: 99%